LEXICOGRAPHIC ANALYSIS OF LINGUISTIC TERMS (ON THE BASIS OF MATERIALS OF EXPLANATORY DICTIONARIES OF THE ENGLISH, RUSSIAN AND UZBEK LANGUAGES) - Izatilloevna, Khodjaeva Dilafruz (International Journal of Psychosocial Rehabilitation, 2020)
This paper analizes Lexicographic analysis of linguistic terms (on the basis of materials of explanatory dictionaries of the English, Russian and Uzbek languages). On this case, theoretical basis of the explanatory dictionaries of the English, Russian and Uzbek were discussed. It is concluded with major features of Lexicographic analysis of linguistic terms.